1994
DOI: 10.1515/znc-1994-9-1015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Systematics of the Nepetoideae (Family Labiatae): Phylogenetic Implications from rbcL Gene Sequences

Abstract: Total DNA was extracted from 41 species (20 genera) of the subfamily Nepetoideae (fam ily Labiatae). Using rbcL-specific primers, the rbcL gene was amplified by polymerase chain reaction (PCR) and sequenced directly. RbcL sequences were evaluated with character state (maximum parsimony; PAUP) and distance methods (neighbour-joining; MEGA). In agree ment with classical systematics all taxa studied cluster within the Nepetoideae and are clearly distinguished from members of the subfamily Lamioideae. A number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 4 publications
2
28
0
1
Order By: Relevance
“…The opposite can be seen for thymine (17.5% and 40.5%, respectively). These findings are in agreement with other rbcL analyses (Kaufmann and Wink 1994;Käss and Wink 1995).…”
supporting
confidence: 93%
“…The opposite can be seen for thymine (17.5% and 40.5%, respectively). These findings are in agreement with other rbcL analyses (Kaufmann and Wink 1994;Käss and Wink 1995).…”
supporting
confidence: 93%
“…2) did not reveal significant differences between G. luteum and the dead-nettle species, and confirmed the results from other studies investigating the chloroplast genome (Kaufmann and Wink, 1995;Sheen et al, 2010;Bendiksby et al, 2011b) which found close relationships between the genera Lamium and Galeobdolon. Sheen et al (2010) proposed to group the two genera with Wiedemannia as part of the tribe Lamieae, and some of the same researchers made them part of the genus Lamium in a subsequent paper (Bendiksby et al, 2011a).…”
Section: Its Regionsupporting
confidence: 87%
“…Studies below the family level have discovered paraphyletic and/or polyphyletic groupings such as the subfamilies Chloanthoideae and Viticoideae, the Satureja L. complex, and Lamium L. (Wink and Kaufmann 1996;Cantino and Wagstaff 1998;Wagstaff et al 1998). In all of these analyses, monophyly of subfamily Nepetoideae and tribe Mentheae is well supported (Kaufmann and Wink 1994;Wagstaff et al 1995). Within tribe Mentheae, Monarda L., Mentha, Nepeta L., and Salvia have been the subject of molecular systematic analyses at the species level (Prather et al 2002;Walker et al 2002;Jamzad et al 2003 ;Bunsawat et al, in mss.).…”
Section: Trusty Et Al: Bystropogon and The New Worldmentioning
confidence: 94%